ADSORPSI ION LOGAM Cd(II) OLEH SBEG-g-PMMA - Maria Paristiowati; Yusmaniar; Ratna Choiryana (Matematika dan Sains, 2011)
The propose of research is to find the capability of the SBEG-g-PMMA to adsorb Cd(II) ion. This research used batch method with various of pH, contact time, and initial concentration of solution. Characterization was conducted by FTIR and AAS. The IR spectrum of the SBEG-g-PMMA showed the presence of carbonil group (C=O) at 1735.4 cm-1 and C-O ester at 1244.14 cm-1. While the optimum adsorption capasity of the SBEG-g-PMMA to Cd(II) ion was obtained at pH of 6, contact time of 10 minutes, and initial concentration of 300 ppm. Adsorption of Cd(II) ion using the SBEG-g-PMMA followed the Langmuir isotherm with maximum adsorption capasity of 47.60 mg/g adsorbent.-1 and C-O ester at 1244.14 cm-1. While the optimum adsorption capasity of the SBEG-g-PMMA to Cd(II) ion was obtained at pH of 6, contact time of 10 minutes, and initial concentration of 300 ppm. Adsorption of Cd(II) ion using the SBEG-g-PMMA followed the Langmuir isotherm with maximum adsorption capasity of 47.60 mg/g adsorbent.